1996
DOI: 10.1074/jbc.271.25.14883
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Functional Characterization of a System ASC-like Na+-dependent Neutral Amino Acid Transporter

Abstract: A cDNA was isolated from mouse testis which encodes a Na ؉ -dependent neutral amino acid transporter. The encoded protein, designated ASCT2, showed amino acid sequence similarity to the mammalian glutamate transporters (40 -44% identity), Na ؉ -dependent neutral amino acid transporter ASCT1 (57% identity; Arriza, J. was typical of amino acid transport system ASC, which prefers neutral amino acids without bulky or branched side chains. ASCT2 also transported L-glutamate at low affinity (K m ‫؍‬ 1.6 mM). L-Gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
428
5
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(483 citation statements)
references
References 40 publications
35
428
5
1
Order By: Relevance
“…HgCl 2 and methylmercury are the most common forms of mercury to which humans are exposed [4,[6][7]; mersalyl has been used as a prototypal hydrophilic mercury compound which is frequently used as a specific reagent for Cys residues of proteins [35]. Preliminary studies performed with hydrophilic SH reagents, suggested that the reconstituted transporter contains thiol groups of cysteine exposed towards the extraliposomal compartment, which corresponds to the extracellular environment; these data correlated well with the predicted hydropathy profile of ASCT2 [27,40]. In this profile 2 Cys residues are located in a large hydrophilic loop exposed towards the extracellular environment (not 12 shown and see ref.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…HgCl 2 and methylmercury are the most common forms of mercury to which humans are exposed [4,[6][7]; mersalyl has been used as a prototypal hydrophilic mercury compound which is frequently used as a specific reagent for Cys residues of proteins [35]. Preliminary studies performed with hydrophilic SH reagents, suggested that the reconstituted transporter contains thiol groups of cysteine exposed towards the extraliposomal compartment, which corresponds to the extracellular environment; these data correlated well with the predicted hydropathy profile of ASCT2 [27,40]. In this profile 2 Cys residues are located in a large hydrophilic loop exposed towards the extracellular environment (not 12 shown and see ref.…”
Section: Discussionmentioning
confidence: 58%
“…In particular it was reported that ASCT1 has the same consensus sequence of Glt Ph and, hence, it may have the same structural fold. As the human ASCT2 and ASCT1 [40], the rat ASCT2 sequence shares 56 % identity with the rat ASCT1 and the same consensus sequences of Glt Ph (not shown) confirming that ASCT2 belongs to the same transporter family. Thus the ASCT2 sequence has been aligned with the Glt Ph and the alignment has been used to construct the homology model (Fig.…”
Section: Page 11 Of 30mentioning
confidence: 81%
“…Moreover, amino acids and amino acid transporters play important roles other than in energy metabolism, such as in macromolecular synthesis, mTOR activation, and ROS homeostasis beyond energy metabolism [49]. There are approximately fifty different types of amino acid transporters, but only LAT1 [50], LAT3 [51], ASCT2 [52], ATB 0, + [53] and xCT [54] have been reported to be expressed at high levels on the surface of cancer cells. Recently, there have been numerous reports in cancer cells related to glutamine transport via ASCT2 and LAT1 [55][56][57].…”
Section: Trans-1-amino-3-[ 18 F]fluorocyclobutanecarboxylic Acid ([mentioning
confidence: 99%
“…Neural retina was isolated from mouse eye, and because ASCT2 is expressed in lung, brain and kidney (Utsunomiya-Tate et al, 1996), these tissues were used as positive controls. Protein was extracted as described (Dunn et al, 2006) and membranes were incubated for 2 h at room temperature with the polyclonal antibody against ASCT2 (1:500).…”
Section: Immunodetection Of Sr and Asct2mentioning
confidence: 99%